Blockchain and other Determinants of the Financial Attractiveness of Tourism Enterprises at the Regional Level: A Proposal for a Synthetic Fundraising Indicator - Prados-Castillo , Juan Francisco; Salinas Fernandez, Jose Antonio; Casas-Jurado, Amalia Cristina (Transformations In Business & Economics, 2025)
This study evaluates the key factors influencing non-traditional financing in the tourism industry as an alternative to traditional bank financing. It explores whether companies using Blockchain technology or integrating it into their processes are more likely to secure investments. Two significant contributions are made: proposing variables that enhance financial attractiveness in tourism and examining whether companies adopting Blockchain attract more investment. Using a sample of 1,327 tourism companies from Crunchbase, this study develops five indicators and constructs a synthetic indicator using the P2 distance method. The results reveal that tourism companies incorporating Blockchain are more likely to secure financing, influencing regional financing capabilities, and enhancing appeal to private investors. The Synthetic Indicator of Fund Raising offers a novel tool for assessing investment potential globally, providing insights into financial attractiveness across regions and highlighting the role of advanced technologies, such as Blockchain, in securing private investments.
Keywords: tourism financing and competitiveness; CrunchBase; regional analysis; synthetic indicator of fund raising; DP2